(untitled) (Progressive Agriculture, 2017)
Histopathology is promising field for research in aquatic toxicology as it provides the real picture of the toxic effects of xenobiotics in vital functions of a living organism. The present study aims to evaluate the toxic effect of pesticide namely profenofos on silver barb. Liver and kidney of silver barb were examined histologically after exposure to sublethal concentrations (0.01 ppm, 10% of LC50 and 0.05 ppm, 50% of LC50) of profenofos for 0, 7, 15 and 30 days. Histological recovery was also studied by maintaining the pesticide‐exposed fish in a freshwater system for an additional 7, 15 and 30 day. Kidney and liver of exposed individuals exhibited some remarkable changes in their histology in comparison to control and recovery group. Hepatic lesions in the liver tissues of fish were characterized by cloudy swelling of hepatocytes, lipoid vacuoles, pycnotic nuclei and focal necrosis. Epithelial hypertrophy, narrowing of the tubular lumen, atrophy of the glomerulus, broader Bowman’s capsule, necrosis in the epithelial cells and pycnosis in the hematopoietic tissue were observed in kidney tissues of experimental fish. These lesions grew with increasing concentration. Although some of the changes were reversible, the rest were less pronounced after a recovery period. Progressive Agriculture 28 (3): 240-248, 2017